Clays and Clay Minerals, Vol. 59, No. 3, 240–249, 2011. - Flores, Jorge; Lima, Enrique; Maubert, Marisela; Aduna, Enrique; Rivera, Jose Luis (My University, 2011)
Toxic dyes must be removed from waste water coming from the textile and paint industries. Adsorption is one possible method of removing dyes under ‘soft’ conditions, without the generation of secondary hazardous materials. The present study used the carbonate-containing layered double hydroxides (LDH), Mg-Al and Mg-Zn-Al (with a M2+/M3+ ratio of 3), as adsorbents to remove two industrial colorants, Astrazon Remazol Brilliant Blue and Direct Red, present in low concentrations in aqueous solutions. The physicochemical properties of adsorbents at the surfaces of LDH, as well as the properties of the solutions containing the dyes control how the colorants are removed. Both fresh and calcined LDH were effective in the removal experiments, with effectiveness ranging from 50 to 100%. Analysis of kinetic data demonstrated that the adsorption process fitted the pseudo-second-order model better than the pseudo-first order model, information which is useful for system design in the treatment of wastes from the textile industry. Parameters such as pH of solutions and concentration of dye in solution influenced mainly the initial adsorption rate.
Clean-up Of Wastes From The Textile Industry Using Anionic Clays
gsccm59303-flo.pdf-- 451KB
Keywords: Periodicals; Geology; Adsorption; Colorant; Dyes; Hydrotalcite; Layered Double Hydroxides; Remediation; Textile Industry; Wastes